2017
DOI: 10.1002/ptr.5990
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐gallate enhances differentiation of acute promyelocytic leukemia cells via inhibition of PML‐RARα and HDAC1

Abstract: The use of all-trans retinoic acid (ATRA) has dramatically improved the treatment and survival rate of patients with acute promyelocytic leukemia (APL). However, toxicity and resistance to this drug are major problems in the treatment of APL with ATRA. Earlier studies have suggested that the green tea polyphenol epigallocatechin gallate (EGCG) induces cell death in hematopoietic neoplasms without adversely affecting normal cells. In the present study, the potential therapeutic effect of EGCG in APL and the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
2
26
0
1
Order By: Relevance
“…We showed that knocking down FASN accelerated ATRA-induced differentiation, while inhibition of its enzymatic function by pharmacological inhibitors such as C75 or Orlistat had no effect. Furthermore, we found that FASN expression activates mTOR We further confirmed that EGCG positively impacts on cellular differentiation in additional AML subtypes in vitro (Britschgi et al, 2010;Moradzadeh et al, 2018;Lung et al, 2002). Searching for potential mediators of the positive effects of EGCG observed during ATRA-induced differentiation, we previously found that EGCG induces expression of the Ca 2+ /calmodulin-regulated serine/threonine kinase DAPK2.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We showed that knocking down FASN accelerated ATRA-induced differentiation, while inhibition of its enzymatic function by pharmacological inhibitors such as C75 or Orlistat had no effect. Furthermore, we found that FASN expression activates mTOR We further confirmed that EGCG positively impacts on cellular differentiation in additional AML subtypes in vitro (Britschgi et al, 2010;Moradzadeh et al, 2018;Lung et al, 2002). Searching for potential mediators of the positive effects of EGCG observed during ATRA-induced differentiation, we previously found that EGCG induces expression of the Ca 2+ /calmodulin-regulated serine/threonine kinase DAPK2.…”
Section: Discussionsupporting
confidence: 67%
“…Given the fact that APL cells treated with EGCG demonstrated improved response to ATRA therapy, we asked if EGCG can be beneficial to other AML subtypes that are refractory to ATRA treatment. We and others previously demonstrated a positive impact of co-treating HL60 AML cells, a non-APL AML cell line that responds to ATRA, with EGCG and ATRA (Britschgi et al, 2010;Moradzadeh et al, 2018;Lung et al, 2002). Therefore, we tested if ATRA-refractory AML cell lines with different genetic backgrounds, namely MOLM-13 (FLT3-ITD + ) and OCI/AML2 (DNMT3A R635W mutation), would respond to ATRA in combination with EGCG.…”
Section: Lowering Fasn Expression Improves Atra Therapy In Non-apl Ammentioning
confidence: 99%
“…PML-RARα homodimers worked synchronously with co-repressors and histone deacetylases (HDACs) and consequentially enhanced DNA methylation [29]. EGCG reduced the levels of HDAC1 and PML/RARα in leukemic cells ( Figure 2) [30].…”
Section: Regulation Of Methylation-associated Machinerymentioning
confidence: 99%
“…However, resistance to these drugs and their toxicity are major problems in the treatment of APL . In the recent years, natural compounds are major subjects for investigating the anticancer drugs with low toxicity and high efficacy . Currently, some of the plant‐derived compounds are widely used for chemotherapy of cancerous patients.…”
Section: Discussionmentioning
confidence: 99%